Effectiveness Of The JKN Mobile Application In Optimizing Waiting Time For BPJS Outpatient Patients - Pratama, Sergil Bhakti; Setiatin, Sali (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
The JKN mobile application offers features such as online registration and real-time notifications to address barriers such as manual registration, but long queue times can reduce service satisfaction and accessibility. This study employed a descriptive qualitative method, aiming to determine how long BPJS Kesehatan patients wait for outpatient services, the factors that cause delays, and whether the JKN mobile application can be optimized. This study used 15 patients as an incidental sample, with percentage analysis divided into categories of <60 minutes and >60 minutes. The results showed that 73.33% (11 patients) met the waiting time standard of less than 60 minutes, while 26.67% (4 patients) exceeded 60 minutes. This was primarily due to the new patient status and lack of space in the surgical polyclinic for 100% of cases. The neurology and orthopedics polyclinics achieved 100% compliance with the standard. This study suggests that the JKN mobile application can accelerate the registration process and reduce queues, supporting the BPJS system and national health policy, and increasing universal accessibility to services. Furthermore, the JKN mobile application, which includes online registration and instant notifications, is being encouraged to expedite the new patient process and optimize resource allocation, particularly in surgical polyclinics. The app aims to improve accessibility and patient satisfaction.